Survival Strategy of Rice Farmers in Planting Paddy in Dry Season - Arsal, Thriwaty; Yunus, Mahmud; Handoyo, Eko; Ahmad, Sakaria (KOMUNITAS: International Journal of Indonesian Society and Culture, 2020)
The development of agricultural tools and technology has made a change to cropping patterns in agricultural communities in Donoyudan Village. Farmers begin to plant rice in the dry season with the help of water wells as the main source of irrigation. Farmers choose to plant rice in the dry season because the results are better than the rainy season. The purpose of the research is to determine the survival strategies of paddy farmers in choosing plant species on agricultural land in the dry season. The research method uses qualitative methods, namely observation, triangulation, and in-depth interviews with farmers and farmer groups. The research is conducted in Donoyudan Village, Kalijambe District, Sragen Regency. The results show that the survival strategy of paddy farmers and rice farming activities in the dry season is the availability of water wells and water pumping machines as the main sources of irrigation in the dry season. Water wells are used if there is not enough rainwater to irrigate the fields. There are two types of water wells, which are shallow well and deep well.